2007
DOI: 10.1089/jmf.2006.076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin on Intracerebroventricular Colchicine-Induced Cognitive Impairment and Oxidative Stress in Rats

Abstract: This study was designed to investigate the protective effects of curcumin against colchicine-induced cognitive impairment and oxidative stress in rats. Male Wistar rats (weighing 150-200 g) received colchicine intracerebroventricularly (15 microg per rat), and cognitive dysfunctions were evaluated by the Morris water maze and the plus maze performance task and supported by biochemical tests. Central administration of colchicine caused memory deficit in both the Morris water maze and the elevated plus maze task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 37 publications
2
20
0
2
Order By: Relevance
“…Curcumin also protects mouse brain from oxidative stress caused by 1-methyl-4-phenyl-1, 2,3,6-tetrahydropyridine [189] and has also been reported to attenuate 3-nitropropionic acid-induced neurotoxicity [190]. In rat brain, curcumin protects against lead- and cadmium-induced lipid peroxidation as well as lead-induced tissue damage [191].…”
Section: Dietary Spices and Admentioning
confidence: 99%
“…Curcumin also protects mouse brain from oxidative stress caused by 1-methyl-4-phenyl-1, 2,3,6-tetrahydropyridine [189] and has also been reported to attenuate 3-nitropropionic acid-induced neurotoxicity [190]. In rat brain, curcumin protects against lead- and cadmium-induced lipid peroxidation as well as lead-induced tissue damage [191].…”
Section: Dietary Spices and Admentioning
confidence: 99%
“…Epidemiologic data has shown that regular curcumin intake may be related to better cognitive function in healthy elderly [3], while in rat models curcumin appears to reverse various forms of cognitive impairment [4], [5], [6], [7], [8], [9]. For example, chronic administration of curcumin can ameliorate age-related spatial memory deficits [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, chronic administration of curcumin can ameliorate age-related spatial memory deficits [10]. These effects may be due to curcumin's activity on oxidative stress [4], [5], [7], BDNF and ERK/P38 kinase signalling pathways [6], degradation of PKCδ [10] or inhibition of histone acetyltransferase [11], as well as several other activities. Curcumin also may protect against Alzheimer's disease (AD) pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Novel antioxidants may offer an effective and safe means of bolstering body's defense against free radicals [11] and thereby provide protection against AD like problems. Various natural antioxidants like curcumin, rosmarinic acid, huperzine A have been reported to have a neuroprotective effect against AD [1214]. Centella asiatica (CA) L. Urban (syn.…”
Section: Introductionmentioning
confidence: 99%